PROBLEMATIKA GURU MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA BELAJAR - Mohammad Faruq Abdullah; Rusdin; Firdiansyah Alhabsyi (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
The issues in Islamic Education in the era of Merdeka Learning have many problems in their implementation. This study aims to analyze the challenges faced by Islamic Education teachers (PAI) in implementing the Merdeka Belajar Curriculum at SMPN 9 Ogodeide. The method used is a descriptive qualitative approach, employing data collection techniques that include observation, interviews, and documentation. Data analysis is conducted using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the challenges faced by PAI teachers can be grouped into three main aspects: the limited understanding of teachers regarding the Merdeka Curriculum, particularly in integrating project-based learning; the limitations in facilities and infrastructure, especially in technology; and the varying levels of teacher readiness and suboptimal school support. Curriculum renewal has a significant impact on the learning process because with this renewal, the processes, models, or methods of learning will be more effective and efficient, and will advance to improve the quality of education in Indonesia to make education in Indonesia better. Curriculum and learning are two interconnected aspects. As a plan or program, the curriculum would be meaningless if it were not implemented in the form of learning. This finding indicates the need for intensive training and support from facilities so that the implementation of the Merdeka Curriculum can run effectively.